2019
DOI: 10.1111/ipd.12571
|View full text |Cite
|
Sign up to set email alerts
|

Does previous application of silver diammine fluoride influence the bond strength of glass ionomer cement and adhesive systems to dentin? Systematic review and meta‐analysis

Abstract: BackgroundSilver diammine fluoride (SDF) applied before a restoration may prevent recurrent caries; therefore, its effect on the bonding of restorative materials is contradictory.AimTo assess through a systematic review and meta‐analysis the influence of SDF on the bonding performance of adhesive materials to dentine.DesignA systematic search was carried out in PubMed, Web of Science, LILACS, and Scopus. Studies comparing bond strength of adhesive systems or glass ionomer cement to SDF‐treated and ‐untreated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The bond strengths of composite to sound primary molars were negligibly affected by the pretreatment of the primary dentin with 38% SDF as cleared by Wu et al while Fröhlich et al in systematic review and meta-analysis (2019) found that the previous application of SDF does not influence the dentine bond strength of GIC but compromises the bonding of adhesive systems [14], [15]. Therefore, the aim of the current study was to evaluate shear bond strength (SBS) of RMGIC to primary dentin after SDF pre-treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond strengths of composite to sound primary molars were negligibly affected by the pretreatment of the primary dentin with 38% SDF as cleared by Wu et al while Fröhlich et al in systematic review and meta-analysis (2019) found that the previous application of SDF does not influence the dentine bond strength of GIC but compromises the bonding of adhesive systems [14], [15]. Therefore, the aim of the current study was to evaluate shear bond strength (SBS) of RMGIC to primary dentin after SDF pre-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cohesive failure within GICs was the most common fracture mode between GICs and dentine in a study done by Tanumiharja et al, whereas this type of failure was less frequent absent in both groups in the present study. This variance might be explained by the different experimental conditions [15], [21].…”
mentioning
confidence: 99%
“…The risk of bias was based on and adapted from a previous study [ 12 ]. To establish the quality of the study, the following parameters were assessed: random assignment of the teeth to the experimental groups, description of sample size calculation, the same number of teeth/specimens per group, restorative materials applied according to the manufacturers’ instructions, materials and testing procedures performed by a single operator, specimens tested by a blinded operator, and failure mode evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…39 Previous application of SDF does not show an influence on bonding strength between GIC and the dentine. 40 SDF is a valuable option of nonsurgical caries management in is COVID-19 era.…”
Section: Restorations After Sdf Therapy?mentioning
confidence: 99%